Aesthetic Literacy in Primary Schools: A Literature Review of the Importance of Art Appreciation from an Early Age - Galih Suryadmaja; Didin Septa Rahmadi; Gading Suryadmaja; Fikhan Ghazali; Azril Irzam; Muhammad Fajar Putranto (Varied Knowledge Journal, 2025)
Aesthetic literacy constitutes a critical yet often underemphasized dimension of primary education, frequently overshadowed by the prioritization of academic cognitive competencies. In fact, aesthetic experiences—particularly through engagement with and appreciation of the arts—play a significant role in cultivating children’s sensitivity, creativity, and reflective capacities from an early age. This article aims to provide a comprehensive examination of the role of art appreciation in the development of aesthetic literacy in primary schools, as well as its implications for pedagogical practices. This study adopts a systematic literature review approach, drawing on a range of relevant scholarly sources in the fields of art education, child development, and aesthetic literacy. The analytical process employs thematic synthesis to identify recurring patterns and conceptual relationships emerging across the literature. The findings indicate that art appreciation contributes simultaneously to children’s cognitive, affective, social, and creative development. Furthermore, aesthetic literacy enriches learning experiences and supports the formation of cultural sensitivity and identity. Its effective implementation in primary education requires the integration of arts-based curricula, the application of multimodal pedagogical approaches, and the active involvement of teachers alongside a supportive learning environment. Therefore, aesthetic literacy should be positioned as an integral component of primary education to foster more holistic, human-centered, and meaningful learning processes.